Chronic cutaneous chromoblastomycosis: A rare case - Earlia, Nanda; Maulida, Mimi; Handriani, Risna; Kamarlis, Reno Keumalazia; Pradistha, Aldilla (UI Scholars Hub, 2024)
Background: Chromoblastomycosis (CBM) is a rare, chronic granulomatous and suppurative skin infection classified as a subcutaneous mycosis. CBM has a poor prognosis with a low cure rate and a high recurrence rate. The lack of scientific data regarding the diagnosis and treatment of CBM also presents a challenge for clinicians in treating this disease. Appropriate therapy can increase the cure rate and prevent disease recurrence. Case Illustration: A 66-year-old woman presented with swelling in her left arm since the last 18 years due to wood-related injuries. There were multiple well-defined hyperkeratotic verrucous plaques, papules, and nodules, measuring 6-10 cm in diameter on the left antebrachial and hand regions. Some lesions were covered with erosion and crusts. The patient also had bone malformation. Histopathological examination showed typical characteristics of CBM. The patient was treated with 100 mg Itraconazole b.i.d. for 8 months. Discussion: Clinical manifestations and histopathological examination showed typical characteristics of CBM. Bone malformation occurred due to complications in chronic cases. Facility limitations led to the inability to perform direct microscopic examination using potassium hydroxide (KOH) and fungal culture on Sabouraud's dextrose agar. After 8 weeks of treatment, the patient's lesions were improved. The patient will be evaluated every month until treatment is complete to monitor the side effects of therapy. Conclusion: CBM lesions were improved after 8 weeks of treatment. Bone malformation could occur in chronic cases. It is important to diagnose CBM correctly and provide adequate therapy for a good outcome.